Siaga Kids: An Educational Game for Enhancing Self-Safety Awareness Among Elementary School Students - Husein Abimanyyu; Chanifah Indah Ratnasari; Septiana Widayanti (Komunitas Dosen Indonesia, 2025)
Safety education is a crucial component of early childhood learning, as elementary school students often have limited ability to identify potential dangers and respond appropriately. Although numerous studies have introduced educational games for safety learning, most focus on a single topic, such as disaster preparedness or traffic safety. There remains a lack of integrated, multi-threat learning media that simultaneously address different types of risks within one child-friendly platform. This study aims to address this gap by developing